A Case of Oncocytic Adrenal Cortical Neoplasm with Uncertain Malignant Potential Turned Out to Be Oncocytic Adrenal Cortical Carcinoma with Distant Metastasis: Could Pathology Do Better Initially? - Chien-Peng Huang; Ming-Shen Dai; Chien-Chang Kao; Wen-Chiuan Tsai; Cheng-Ping Yu (Medicina, 2022)
Oncocytic adrenal cortical neoplasms are rare cases and are divided into oncocytoma, oncocytic neoplasms of uncertain malignant potential and oncocytic adrenal cortical carcinomas, based on the Lin–Weiss–Bisceglia (LWB) histological system adopted in the current World Health Organization (WHO). We reported a 42-year-old female diagnosed with an oncocytic neoplasm of uncertain malignant potential initially, which turned out to be a carcinoma owing to distant metastasis to the scalp and lung. To our knowledge, this is the first published case of oncocytic adrenal cortical carcinoma with scalp metastasis. This case also highlights the limitation of the current diagnostic algorithm and emphasizes the importance of two parameters (PHH3 and Ki-67) for determining the malignant potential of oncocytic adrenal cortical neoplasms.